Harvest of All-Soft Tissue Quadriceps Tendon Autograft for Anterior Cruciate Ligament Reconstruction With or Without Closure of Resulting Defect Has No Effect on Patellar Height - Mitchell C. Parker, B.S; Sarah D. Lang, M.E.d, A.T.C; Harrison Lakehomer, M.D; Steve O'Neil, M.D; Timothy S. Crall, M.D; Brian B. Gilmer, M.D (Elsevier, 2023)
Purpose: To evaluate the radiographic effect of quadriceps tendon harvest on patellar height and to determine whether closure of a quadriceps graft harvest defect resulted in a significant change in patellar height compared to nonclosure. Methods: We conducted a retrospective review of prospectively enrolled patients. The institutional database was queried and all patients who underwent quadriceps autograft anterior cruciate ligament reconstruction between 2015 and March 2020 were included. Graft harvest length in millimeters and final graft diameter after preparation for implantation were obtained from the operative record and demographic data were obtained from the medical record. Radiographic analysis was performed of eligible patients using standard ratios of patellar height: Insall-Salvati (IS), Blackburn-Peele (BP), and Caton-Deschamps (CD). Measurements were performed using digital calipers on a digital imaging system by 2 postgraduate fellow surgeons. Preoperative and postoperative radiographs were performed at 0° according to a standard protocol. Postoperative radiographs were performed 6 weeks postoperatively in all cases. Preoperative patellar height ratios were compared with postoperative patellar height ratios for all patients using t-tests. Subanalysis was then performed to compare the effect of closure of with nonclosure on patellar height ratios using repeated-measures analysis of variance. Interrater reliability between the 2 reviewers was assessed using an intraclass correlation coefficient calculation. Results: In total, 70 patients met final inclusion criteria. There were no statistically significant changes from pre- to postoperative values for either reviewer for IS (reviewer 1, P = .47; reviewer 2, P = .353), BP (reviewer 1, P = .98; reviewer 2, P = .907), or CD (reviewer 1, P = .107; reviewer, 2 P = .188). The closure and nonclosure groups were adequately powered and no statistically significant demographic differences between the closure and nonclosure groups was identified for sex (P = .066), age (P = .343), weight (P = .881), height (P = .42), laterality (P = 1), meniscal repair (P = .332), graft diameter (P = .068), or graft length (P = .183). According to the repeated measures analysis of variance, closure of the quadriceps defect had no significant impact on any of the knee ratios. However, reviewer identity had a significant influence on the CD ratio. Intraclass correlation coefficient analysis revealed excellent agreement between reviewers for the IS (0.982) and BP (0.954) ratios, but only moderate-to-good agreement for the CD (0.751) ratio. Conclusions: Harvest of quadriceps tendon graft does not result in radiographic changes in patellar height. Furthermore, closure of the quadriceps defect does not appear to result in radiographic changes in patellar height. Level of Evidence: III, retrospective comparative trial.